PENGUJIAN MIKROORGANISME LOKAL ( MOL) LIMBAH SAYURAN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI ( Brassica juncea L) - Sri Utami Lestari; Neng Susi; Enny Mutryarny (Jurnal Ilmiah Pertanian, 2017)
Nowadays people are increasingly concerned about the importance of product quality. The use of fertilizers derived from organic materials is believed to bring more benefits to agricultural products where products become healthier, environmentally friendly and can reduce the negative impact of chemicals that are harmful to humans and the environment. Veg mole is expected in addition to its local microorganisms also Nitrogen element content can increase the growth and production of mustard plants.The purpose of this study is to determine the effect and to get a good dose of MOL vegetable waste on the growth and production of mustard plants.The experiment was conducted experimentally using non factorial completely Randomized Design (RAL) consisting of 5 treatment levels and 4 replications to obtain 20 experimental units. Each plot consists of 16 plants and 4 plants as sample. The level of treatment is as follows: Mo: Without giving MOL of vegetable waste, M1: Giving MOL vegetable waste 75 cc / l water, M2: Giving of MOL vegetable waste 150 cc / l water, M3: Giving MOL vegetable waste 225 cc / l water , M4: Giving MOL vegetable waste 300 cc / l waterThe result of this research can be concluded that vegetable MOL has no significant effect on all observed parameters, ie plant height (cm), number of leaf (strands), leaf length (cm), leaf width (cm), wet weight (g) consumption (g).